Narrowing of glacial isthmus between Sørkapp Land and Torell Land, southern Spitsbergen, 1900–2023 - Michał Pawłowski; Krzysztof Ostafin (Journal of Maps)
The paper provides a comprehensive overview of the transformation of the glacial isthmus between Sørkapp Land (southern peninsula) and the remainder of Spitsbergen from 1900 to 2023. The region distinguishes itself with notable environmental and landscape transformations since the early twentieth century, the post-Little Ice Age. These ongoing transformations are poised to swiftly convert the Sørkapp Land peninsula into an island, driven by the decline of the glacial isthmus connecting Sørkapp Land to the rest of Spitsbergen. Key policy highlightsRecession of glaciers is making Sørkapp Land one of the ‘hotpoints’ of environmental changes.The glacial isthmus between Sørkapp Land and Torell Land is shrinking and its minimum width is currently about 4 kilometres.Complete melting of glacial isthmus will create new large island and transform Hornsund and Hambergbukta into a strait.